2014
DOI: 10.1002/j.0022-0337.2014.78.2.tb05673.x
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Stress in Dental Students

Abstract: The aim of this study was to systematically review the available literature on the levels, causes, and impact of stress among dental students. The investigators searched eight electronic databases: Medline, Medline in process, Psychinfo, ERIC, Embase, Cochrane Library, Web of Science, and SCOPUS. Two independent reviewers conducted the selection, data extraction, and quality appraisal for included studies. The investigators then coded both quantitative and qualitative studies using similar codes and pooled res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
346
7
19

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(393 citation statements)
references
References 99 publications
(148 reference statements)
21
346
7
19
Order By: Relevance
“…Whereas more research is focusing on the health and well‐being of graduate students, far less has focused specifically on health sciences professional graduate students, who may be at a unique risk for adverse mental health concerns due to high levels of stress and burnout as well as the rigor of their academic programs (Dyrbye et al, ; Elani et al, ). Health sciences programs typically include nursing, medicine, dentistry, health and rehabilitation sciences, optometry, pharmacy, social work, and veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas more research is focusing on the health and well‐being of graduate students, far less has focused specifically on health sciences professional graduate students, who may be at a unique risk for adverse mental health concerns due to high levels of stress and burnout as well as the rigor of their academic programs (Dyrbye et al, ; Elani et al, ). Health sciences programs typically include nursing, medicine, dentistry, health and rehabilitation sciences, optometry, pharmacy, social work, and veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…A high level of stress at baseline and incremental increases throughout their education was found amongst dental students in several dental schools in Northern and Western Europe . Multicountry studies showed that the perceived source of stress varied greatly amongst dental students in different countries; clinical training was one of the main stressors according to two systematic reviews . A recent study in France identified high clinical task quotas and overly stressful examinations as stressors in clinical education …”
Section: Introductionmentioning
confidence: 99%
“…The perception of the educational environment differs from student to student. Most studies show that dental education is a demanding process that creates numerous sources of stress for the students . Academic factors, such as grades and workload, represent the greatest source of stress for students regardless of their year of study .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies show that dental education is a demanding process that creates numerous sources of stress for the students . Academic factors, such as grades and workload, represent the greatest source of stress for students regardless of their year of study . Nevertheless, the students in the first and last year experience the greatest stress .…”
Section: Introductionmentioning
confidence: 99%